The Mathers : three generations of Puritan intellectuals, 1596-1728 - Middlekauff, Robert (University of California Press, 1999)
In this classic work of American religious history, Robert Middlekauff traces the evolution of Puritan thought and theology in America from its origins in New England through the early eighteenth century. He focuses on three generations of intellectual ministers--Richard, Increase, and Cotton Mather--in order to challenge the traditional telling of the secularization of Puritanism, a story of faith transformed by reason, science, and business. Delving into the Mathers' private papers and unpublished writings as well as their sermons and published works, Middlekauff describes a Puritan theory of religious experience that is more creative, complex, and uncompromising than traditional accounts have allowed. At the same time, he portrays changing ideas and patterns of behavior that reveal much about the first hundred years of American life.
Keywords: Mather, Richard, -- 1596-1669.; Mather, Increase, -- 1639-1723.; Mather, Cotton, -- 1663-1728.; Mather, Cotton, -- 1663-1728; Mather, Increase, -- 1639-1723; Mather, Richard, -- 1596-1669; Puritans -- Massachusetts -- Biography.; Massachusetts -- Intellectual life -- 17th century.; Massachusetts -- Intellectual life -- 18th century.; Puritains -- Massachusetts -- Biographies.; Massachusetts -- Vie intellectuelle -- 17e siècle.; Massachusetts -- Vie intellectuelle -- 18e siècle.; RELIGION -- Christianity -- Presbyterian.; BIOGRAPHY & AUTOBIOGRAPHY -- Religious.; HISTORY -- United States -- General.; Intellectual life; Puritans; Massachusetts; 1600-1799; 18th century.; american history.; baptism.; biography.; boston.; christian history.; christian.; church doctrine.; church history.; colonial america.; colonies.; cotton mather.; early american history.; faith.; history.; increase mather.; massachusetts.; new england.; nonfiction.; preacher.; puritans.; reason.; religion.; religious experience.; religious history.; richard mather.; science.; sermons.; spirituality.; theology.; witch trials.; Biographies